2003
DOI: 10.1210/en.2002-220690
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase and c-Src, But Not Jun N-Terminal Kinase, Are Involved in Basal and Gonadotropin-Releasing Hormone-Stimulated Activity of the Glycoprotein Hormone α-Subunit Promoter

Abstract: Addition of a GnRH agonist (GnRH-A) to alphaT3-1 cells stimulates different MAPK cascades: ERK, Jun N-terminal kinase (JNK), and p38. Activation of JNK, ERK, and p38 shows a unique fold activation ratio of 25:12:2, which might encode signal specificity. ERK is translocated to the nucleus within 20 min with a peak at 120 min of GnRH-A stimulation. We used the human alpha-subunit promoter linked to chloramphenicol acetyl transferase (alphaCAT) to examine the role of ERK, JNK, and c-Src, which is implicated in MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…9 and 31). Studies from our laboratories have shown that the signaling of GnRH in ␣T3-1 cells involves a direct activation of Raf-1 by PKC, and this step is partially dependent on a second pathway consisting of Ras activation downstream of dynamin and c-Src (32)(33)(34). The activation of JNK in these cells is also mediated primarily by PKC that further induces the sequential activation of c-Src and CDC42/RAC (35).…”
mentioning
confidence: 99%
“…9 and 31). Studies from our laboratories have shown that the signaling of GnRH in ␣T3-1 cells involves a direct activation of Raf-1 by PKC, and this step is partially dependent on a second pathway consisting of Ras activation downstream of dynamin and c-Src (32)(33)(34). The activation of JNK in these cells is also mediated primarily by PKC that further induces the sequential activation of c-Src and CDC42/RAC (35).…”
mentioning
confidence: 99%
“…The answer may rest in either the differential activation of signaling systems within the gonadotrope and/or synthesis, modification, and degradation of either transcription factors or regulatory proteins. It is well established that members of the mitogen activated protein kinase (MAPK) family of signaling proteins are stimulated by GnRH in vivo (50), in cultured rat pituitary fragments (22) and in L␤T2 cells (9,31) to contribute to regulation of gonadotropin subunit gene expression. In particular, activation of phosphorylated extracellular signal-regulated kinases (pERK) 1/2 is more rapid and more sustained in L␤T2 cells perifused with low, rather than high, GnRH pulse frequencies, suggesting that pERK is important in the preferential increase of FSH␤ transcription observed at low GnRH pulse frequency (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the endogenous mouse GnRHRs of gonadotrope lineage ␣T3-1 cells act primarily via activation of PKC and entry of Ca 2ϩ to cause a Raf-1-dependent activation of ERK (40,41). In these cells, EGF receptor trans-activation is not required (42,43), whereas ERK activation by mouse GnRHRs stably transfected into COS7 cells is dependent upon EGF receptor trans-activation (44). In the HeLa cell model used here, both receptors increase pp-ERK1/2 (as measured by Western blotting or immunohistochemistry) (Figs.…”
Section: Discussionmentioning
confidence: 99%